A Tandem In Situ Peptide Cyclization through Trifluoroacetic Acid Cleavage1. Issue 36 (14th May 2014) - Chandra, Koushik; Roy, Tapta Kanchan; Shalev, Deborah E.; Loyter, Abraham; Gilon, Chaim; Gerber, R. Benny; Friedler, Assaf
Abstract We present a new approach for peptide cyclization during solid phase synthesis under highly acidic conditions. Our approach involves simultaneous in situ deprotection, cyclization and trifluoroacetic acid (TFA) cleavage of the peptide, which is achieved by forming an amide bond between a lysine side chain and a succinic acid linker at the peptide N‐terminus. The reaction proceeds via a highly active succinimide intermediate, which was isolated and characterized. The structure of a model cyclic peptide was solved by NMR spectroscopy. Theoretical calculations support the proposed mechanism of cyclization. Our new methodology is applicable for the formation of macrocycles in solid‐phase synthesis of peptides and organic molecules.